Minimizing D.C. Metrorail Disturbances: A Multi-Objective Decision Making Analysis Framework for Strategic Resilience - Foley, Claire; Walker, Amaya; Yang, Ziqian; Mohammed, Salah; Dano, Eric; Jachimowicz, Adam (Systems and Information Engineering Design, SIEDS, IEEE Symposium, 2024)
The Washington Metropolitan Area Transit Authority (WMATA) faces frequent disruptions in its metro system, impacting operational efficiency and rider satisfaction. WMATA's disruptions are categorized into 12 incident levels from A1 (most severe) to D3 (least severe). This research introduces an analytical framework to determine which incident level's disturbances should be mitigated to minimize both downtime and costs due to disturbances. The number of occurrences and total downtime for each incident level were found through data processing on the 18 months of logged disturbances. Multiple WMATA Subject Matter Experts (SMEs) conducted an Analytic Hierarchy Process (AHP) assessment to determine the relative disturbance costs. These costs were subsequently converted into actual costs for all incident levels, leveraging known D2 incident costs. An exploratory interview was performed with WMATA SMEs to obtain weights for the importance of disturbance downtime relative to the cost. The resulting weights were applied to separate normalized downtime and cost scores to yield a ranked list of incident levels that need to be prioritized to best reduce disturbance downtime and cost. These findings directly allow WMATA to prioritize disruption mitigation and ensure operational continuity, benefiting WMATA and its stakeholders.